Central bank mandates and monetary policy stances: Through the lens of Federal Reserve speeches - Christoph Bertsch; Isaiah Hull; Robin L. Lumsdaine; Xin Zhang (Sveriges Riksbank, 2022)
When does the Federal Reserve deviate from its dual mandate of pursuing the economic goals of maximum employment and price stability and what are the consequences? We assemble the most comprehensive collection of Federal Reserve speeches to-date and apply state-ofthe-art natural language processing methods to extract a variety of textual features from each paragraph of each speech. We find that the periodic emergence of non-dual mandate related discussions is an important determinant of time-variations in the historical conduct of monetary policy with implications for asset returns. The period from mid-1996 to late2010 stands out as the time with the narrowest focus on balancing the dual mandate. Prior to the 1980s there was a outsized attention to employment and output growth considerations, while non dual-mandate discussions centered around financial stability considerations emerged after the Great Financial Crisis. Forward-looking financial stability concerns are a particularly important driver of a less accommodative monetary policy stance when Fed officials link these concerns to monetary policy, rather than changes in banking regulation. Conversely, discussions about current financial crises and monetary policy in the context of inflation-employment themes are associated with a more accommodative policy stance.
Keywords: C63; D84; E32; E7; 330; Natural Language Processing; Machine Learning; Central Bank Communication; Financial Stability; Zero Shot Classification; Extractive Question Answering; Semantic Textual Similarity